2019
DOI: 10.18176/jiaci.0316
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Asthma: Key Clinical Questions

Abstract: Obesity is an asthma common comorbidity and is associated not only with its development, but also with a poorer control and higher severity of it. Recent prospective evidence supports the idea that body weight gain precedes the development of asthma, but the debate is far from over. The objective of this document is to conduct a systematic review of 3 clinical questions related to asthma and obesity: 1. Obesity and asthma: the chicken or the egg? Clinical insights from epidemiological and phenotypes studies. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 80 publications
0
19
0
5
Order By: Relevance
“…Como ha sido descrito previamente 7,[17][18][19] , la obesidad es un factor de riesgo no solo para el desarrollo de asma, sino también se asocia a un peor control de dicha patología. En este contexto, un paciente asmático, y que además es obeso, representa un gran desafío clínico debido a la heterogeneidad que presentan ambas patologías 4 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Como ha sido descrito previamente 7,[17][18][19] , la obesidad es un factor de riesgo no solo para el desarrollo de asma, sino también se asocia a un peor control de dicha patología. En este contexto, un paciente asmático, y que además es obeso, representa un gran desafío clínico debido a la heterogeneidad que presentan ambas patologías 4 .…”
Section: Discussionunclassified
“…Finalmente, pese a que diferentes mecanismos biológicos y no biológicos han sido propuestos para explicar la relación existente entre asma y obesidad, aún no está claro si el papel de la obesidad sería inducir el desarrollo de asma o actuar como una comorbilidad 4,13 . Lo que sí está claro es que el aumento de la masa grasa en el abdomen y en la pared torácica reduce la capacidad residual pulmonar, lo que trae como consecuencia la disminución del músculo liso de la vía aérea 27 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The prevalence of both obesity and bronchial asthma (BA) is increasing now as well as their comorbidity [1]. The problem of asthma and obesity has been studied since 1999, when it was found that overweight people have a higher risk of asthma development.…”
mentioning
confidence: 99%